Homestead gardening for year-round vegetable production (Bangla) - Ahmed, Sharif; Miajy, Abu Abdullah; Manik, Md. Zannatul Ferdous (International Rice Research Institute, 2025)
This document explores the potential of homestead gardening as a sustainable strategy for ensuring year-round vegetable production in Bangladesh. Homestead gardens, managed at the household level, provide a reliable source of nutritious vegetables, thereby improving dietary diversity, food security, and income generation. The model uses low-cost, simple techniques suitable for small spaces. It is particularly accessible to women, who play a vital role in household nutrition and food production. The document provides practical steps for establishing and maintaining productive gardens, including site selection, vegetable selection, and other management practices. Promoting homestead gardening not only enhances household nutrition security by providing fresh, healthy vegetables year-round but also empowers women by involving them directly in food production activities. This approach fosters community resilience, supports healthy eating habits, and reduces dependency on external markets. The objective of this knowledge product is to assist farmers, extension workers, and policymakers in scaling up homestead gardening initiatives. It aims to promote sustainable food systems, gender empowerment, and healthy lifestyles throughout Bangladesh. Ultimately, the widespread adoption of this model can improve nutritional outcomes and strengthen household livelihoods.